Efficacy of Tubal Surgery for Permanent Contraception: Considerations for the Clinician - Tasset J; Jensen JT (Dove Medical Press, 2023)
Julia Tasset, Jeffrey T Jensen Department of Obstetrics and Gynecology, Oregon Health & Sciences University, Portland, OR, USACorrespondence: Julia Tasset, Department of Obstetrics and Gynecology, Oregon Health & Sciences University, 3181 SW Sam Jackson Park Road, Mailstop L466, Portland, OR, 97239, USA, Tel +1 503 494 9556, Fax +1 503 494 2391, Email tasset@ohsu.eduAbstract: Permanent contraception meets the needs of many people certain in their decision to never become pregnant in the future. Female permanent contraception procedures became more common than male procedures during the 1970s and 1980s, when laparoscopic surgery became widely available. To better understand the efficacy of these new procedures, the US Centers for Disease Control and Prevention conducted a prospective cohort study, known as the Collaborative Review of Sterilization (CREST). For decades, results of this study have defined perioperative counseling around failure risks of such surgeries. However, laparoscopic technology and techniques have changed significantly in recent decades and evidence has emerged supporting noncontraceptive benefits of tubal excision. Therefore, we present here a review of updated information regarding permanent contraception failure in the modern context and implications for clinical practice and future research directions.Keywords: permanent contraception, gynecology, birth control